The Redox Communication Network as a Regulator of Metabolism - Corkey, Barbara E.; Deeney, Jude T. (Frontiers in Physiology, 2020)
Key tissues are dysfunctional in obesity, diabetes, cardiovascular disease, fatty liver and other metabolic diseases. Focus has centered on individual organs as though each was isolated. Attention has been paid to insulin resistance as the key relevant pathosis, particularly insulin receptor signaling. However, many tissues play important roles in synergistically regulating metabolic homeostasis and should be considered part of a network. Our approach identifies redox as an acute regulator of the greater metabolic network. Redox reactions involve the transfer of electrons between two molecules and in this work refer to commonly shared molecules, reflective of energy state, that can readily lose electrons to increase or gain electrons to decrease the oxidation state of molecules including NAD(P), NAD(P)H and thiols. Metabolism alters such redox molecules to impact metabolic function in many tissues, thus, responding to anabolic and catabolic stimuli appropriately and synergistically. It is also important to consider environmental factors that have arisen or increased in recent decades as putative modifiers of redox and reactive oxygen species (ROS) and thus metabolic state. ROS are highly reactive, controlled by the thiol redox state and influence the function of thousands of proteins. Lactate (L) and pyruvate (P) in cells are present in a ratio of about 10 reflective of the cytosolic NADH to NAD ratio. Equilibrium is maintained in cells because lactate dehydrogenase is highly expressed and near equilibrium. The major source of circulating lactate and pyruvate is muscle, although other tissues also contribute. Acetoacetate (A) is produced primarily by liver mitochondria where ß-hydroxybutyrate dehydrogenase is highly expressed, and maintains a ratio of ß-hydroxybutyrate (ß) to A of about 2, reflective of the mitochondrial NADH to NAD ratio. All four metabolites as well as the thiols, cysteine and glutathione, are transported into and out of cells, due to high expression of relevant transporters. Our model supports regulation of all collaborating metabolic organs through changes in circulating redox metabolites, regardless of whether change was initiated exogenously or by a single organ. Validation of these predictions suggests novel ways to understand function by monitoring and impacting redox state.